An assessment on the future development of high-entropy alloys: Summary from a recent workshop. (November 2015) - Lu, Z.P.; Wang, H.; Chen, M.W.; Baker, I.; Yeh, J.W.; Liu, C.T.; Nieh, T.G.
Abstract: There is increasing interest in both relating the mechanical behavior of high-entropy alloys to their microstructural evolution and in their development for various applications. A special two-day international workshop on the above topic was held in Guiyang, China, in December 2014. The workshop gathered scientists and engineers to exchange information on recent progress in high-entropy alloys, to discuss the scientific issues and challenges to foster international collaborations, and to identify future directions. In this paper, a summary of this workshop is presented, including aspects of definition/terminology, phase formation, microstructure and phase stability, strengthening mechanisms, and high-temperature properties. Future research directions are also outlined. Graphical abstract: Highlights: Recent progress in several critical topics of the high-entropy alloys was briefly summarized. Special emphasis was placed on the relationship between mechanical properties and microstructure. Future research directions of the discussed areas in HEAs are also outlined.